Grado de contaminación bacteriana en el área de quirófano del Hospital Luis Moscoso del cantón Piñas en el período septiembre octubre del año 2005. - Loayza Jaramillo, Andrea K. (2006)
A hospital infection is that is not present or in incubation when a patient is interned in a hospital. And these they can be endogenous or exogenous the endogenous ones are caused by present organisms as part of the patient´s normal flora the second are those caused by organisms acquired by exhibition to the personnel of the hospital, medical devise or polluted atmosphere.